Preparation method of solvent-corrosion-resistant and high-heat-sealing-strength coating film for packaging
By combining modified polyvinylidene chloride emulsion and inorganic nanosilicon dioxide, combined with plasma generator and infrared drying technology, the problems of swelling damage and low heat sealing strength of coated films in an aggressive solvent environment are solved. Achieves high heat sealing and solvent resistant packaging performance.
Patent Information
- Application Number
- CN202411247218.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-31
AI Technical Summary
The existing packaging coating films are easily swelled and damaged under the environment containing an aggressive solvent or aromatic agent, have low heat sealing strength, poor peeling strength, and are prone to adhesion during the preparation process, affecting performance.
The modified polyvinylidene chloride emulsion and inorganic nanosilica solution are used for high-speed dispersion and mixing, combined with plasma generator processing and infrared drying technology, a high crystallinity and dense coating is formed, and the film is improved through improved maturation technology. heat sealing and peel strength.
It significantly improves the heat sealing strength and peeling strength of the coating, prevents solvent erosion, avoids adhesion, and meets the packaging needs of high heat sealing and solvent resistant.
Smart Images

Figure CN119219960A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of coating films for packaging, and in particular relates to a method for preparing a coating film for packaging with high heat-sealing strength and resistance to solvent corrosion. Background Art
[0002] In the prior art, the coated film for packaging is a PET coated film made by first coating a layer of polyurethane glue and then a layer of polyvinylidene chloride (PVDC) on the surface of a biaxially oriented polyester film (BOPET) after chemical treatment or corona treatment, and then aging at a preset time and temperature. This film has certain oxygen and moisture barrier properties, can extend the shelf life of food, and is suitable for food packaging.
[0003] However, the current biaxially oriented polyester film is rarely used directly in packaging of items containing corrosive solvents or aromatics. In addition, this film can be divided into two types: single-sided coating and double-sided coating. Single-sided coating is coating on only one surface of the biaxially oriented polyester film (BOPET), and double-sided coating is coating on both surfaces of the biaxially oriented polyester film (BOPET). The current biaxially oriented polyester film still has the following defects in actual use:
[0004] 1. The existing polyvinylidene chloride (PVDC) coating of the coating film will be gradually swollen by corrosive solvents or aromatics, causing the coating to crack, and in severe cases, the coating will fall off. The main reason is that the double-sided PET coating has low crystallinity, a fluffy surface, is not dense enough, and has a large number of fine cracks. Solvents or aromatics can easily penetrate into the coating, swelling the coating, and causing the coating to crack or even fall off.
[0005] 2. The polyvinylidene chloride (PVDC) coating of the existing coating film can be sealed at a certain temperature. Under the same conditions, its heat sealing strength is low, generally below 2.0N / 25mm, and is not suitable for direct bag packaging.
[0006] 3. The polyvinylidene chloride (PVDC) coating of the existing coating film has poor adhesion and low peel strength under the same conditions, generally below 1.5N / 15mm. The coating is easy to peel off, that is, the coating surface and the PET surface are separated and delaminated.
[0007] 4. During the preparation process of the existing coating film, the film surface will produce adhesion, which will damage the surface of the polyvinylidene chloride (PVDC) coating, that is, the coating surface becomes rough, commonly known as "hair pulling". Therefore, the polyvinylidene chloride (PVDC) coating is more susceptible to erosion and damage by solvents or aromatics.
[0008] In view of the above technical problems, the existing conventional solutions are as follows:
[0009] 1. To address the problem that the film surface will be corroded and damaged by solvents or aromatics, the current method is to extend the aging time of the coated film and increase the aging temperature to increase the crystallinity of the polyvinylidene chloride (PVDC) coating and make the coating dense. However, under this method, the film coating will still be swollen and damaged by solvents or aromatics at a certain time and temperature.
[0010] 2. The heat-sealing performance of the coated film is determined by the properties of the polyvinylidene chloride (PVDC) material itself. Currently, the method of increasing the coating thickness is used to improve the heat-sealing strength of the film. The heat-sealing strength is below 2.0N / 25mm, and the film seal is easy to detach, which cannot meet the bagging requirements.
[0011] 3. The coating of the coated film is easy to peel and delaminate. The method commonly used at present is to chemically treat or corona treat the surface of the film to increase the polarity and roughness of the PET film surface to enhance the bonding strength between PET and polyurethane glue. However, its peel strength is below 1.5N / 15mm. After the coating is compounded with other materials, the composite film is easy to detach at the coating interface under the action of external force, which cannot meet the compounding requirements.
[0012] 4. The adhesion of the coating film during the preparation process is currently treated by adding a certain amount of organic anti-adhesive agents and inorganic anti-adhesive agents. However, organic anti-adhesive agents will reduce the heat sealing performance, oxygen barrier and moisture barrier properties of the coating. At the same time, organic anti-adhesive agents have precipitates, which stick to the guide rollers or pressure rollers of the production equipment, causing serious impact on subsequent processing; inorganic anti-adhesive agents have large particle sizes, generally 2-10 microns, large specific surface area, easy to agglomerate, difficult to disperse, which will cause the film's barrier properties and optical properties to decline. Summary of the invention
[0013] The purpose of the present invention is to provide a method for preparing a coating film for packaging with high heat-sealing strength and resistance to solvent erosion, so as to solve the technical defects in the production process of the coating film for packaging articles containing corrosive solvents or aromatics.
[0014] To achieve the above object, the present invention provides the following technical solutions:
[0015] A method for preparing a solvent-resistant, high-heat-seal strength coating film for packaging, comprising the following steps:
[0016] S1. Prepare a modified polyvinylidene chloride emulsion, wherein the modified polyvinylidene chloride emulsion comprises 80-89 parts by weight of a copolymerized vinylidene chloride emulsion having a solid content of 40%-50% in a polymerization degree, 10 parts by weight of distilled water, and 1-10 parts by weight of an accelerator.
[0017] S2. Prepare an inorganic nano-silica solution, which includes 1-10 parts by weight of inorganic nano-silica, 87-98.9 parts by weight of distilled water, and 0.1-3 parts by weight of an emulsifier, and is mixed by high-speed ball milling. The particle size of the inorganic nano-silica is 7-40 nanometers. Because it is extremely fine and easily clumps together, high-speed ball milling must be used when mixing with water.
[0018] S3. Prepare a coating solution, which includes 90-99.5 parts by weight of the modified polyvinylidene chloride emulsion obtained in S1 and 0.5-10 parts by weight of the inorganic nano-silicon dioxide solution obtained in S2, which are dispersed and mixed at high speed.
[0019] S4. Prepare polyurethane glue, which includes 10-40 parts by weight of a polyurethane main agent, 2-8 parts by weight of a polyurethane curing agent, and 40-100 parts by weight of ethyl acetate, and is dispersed and mixed at a low speed.
[0020] S5. The coating liquid obtained in S3 is coated on the surface of the biaxially oriented polyester film treated by a plasma generator and pre-coated with the polyurethane glue obtained in S4 by a coating machine, and a coated film is prepared by infrared dehydration and hot air drying.
[0021] The coating film obtained by the above preparation method has high crystallinity and dense crystals. The coating will not be swollen and damaged by various solvents or fragrances, and the coating has excellent heat sealing strength and peeling strength. It is suitable for direct bag packaging and can also meet the packaging of items containing corrosive solvents or fragrances.
[0022] As a preferred embodiment of the present invention, the biaxially stretched polyester film is divided into single-sided coating and double-sided coating. Single-sided coating is to coat the coating liquid obtained by S3 on any one surface of the biaxially stretched polyester film, and double-sided coating is to coat the coating liquid obtained by S3 on both sides of the biaxially stretched polyester film.
[0023] As a preferred embodiment of the present invention, the specific method for preparing the modified polyvinylidene chloride emulsion in step S1 is as follows:
[0024] S11. Add 80-89 parts by weight of polyvinylidene chloride emulsion into a stainless steel reactor containing 10 parts by weight of distilled water with stirring, raise the temperature to 35°C, control the pressure at normal pressure, control the frequency of the agitator at 50Hz, and the feeding rate at 45KG / h. After the feeding is completed, keep the temperature and speed constant for 30 minutes.
[0025] S12, keeping the temperature and the frequency of the agitator unchanged, slowly add 1-10 parts by weight of the accelerator to the solution obtained in the above S11, the feeding rate is 10KG / h, and after the feeding is completed, keep the temperature and speed constant for 24 hours, mix evenly, evacuate at low pressure, degas, make a modified polyvinylidene chloride emulsion, and cool to 20°C.
[0026] As a preferred embodiment of the present invention, the specific method for preparing the inorganic nano-silicon dioxide solution in step S2 is as follows:
[0027] Inorganic nano silicon dioxide with a content of 1-10 parts by weight and a particle size of 7-40 nanometers is ground at a low speed and added to a grinder containing 87-98.9 parts by weight of distilled water, the temperature is raised to 40°C, the pressure is controlled at normal pressure, the frequency of the grinder is controlled at 20Hz, the feeding speed is 10KG / h, and after the feeding is completed, the temperature and speed are kept constant for 30 minutes. An emulsifier with a content of 0.1-3 parts by weight is slowly added to the above solution at a feeding speed of 10KG / h. After the feeding is completed, the temperature and speed are kept constant for 30 minutes. The frequency of the grinder is increased to 50Hz within 1-5 minutes, and the temperature and speed are kept constant for 60 minutes. After the inorganic nano silicon dioxide is fully and evenly dispersed, low-pressure vacuuming is performed to degas, and an inorganic nano silicon dioxide solution is prepared, which is then cooled to 20°C.
[0028] As a preferred embodiment of the present invention, the specific method for preparing the coating solution in step S3 is as follows:
[0029] An inorganic nano-silicon dioxide solution with a content of 0.5-10 parts by weight is added to a reaction kettle containing a content of 90-99.5 parts by weight of a modified polyvinylidene chloride emulsion with low-speed stirring, the temperature is raised to 35°C, the pressure is controlled at normal pressure, the stirrer frequency is controlled at 30Hz, the feeding rate is 5KG / h, and after the feeding is completed, the temperature and speed are kept constant for 10 minutes, the stirrer frequency is gradually increased to 50Hz within 1-2 minutes, and the temperature and speed are kept constant for 30 minutes. After mixing evenly, vacuum is evacuated at low pressure, degassing is performed to prepare a coating liquid, and the coating liquid is cooled to 20°C.
[0030] As a preferred embodiment of the present invention, the specific method for preparing the polyurethane glue in step S4 is as follows:
[0031] 10-40 parts by weight of a polyurethane glue main agent with a solid content of 40%-60% is added to a reactor containing 40-100 parts by weight of ethyl acetate with low-speed stirring, at room temperature and pressure, the stirrer frequency is controlled at 20 Hz, the feeding speed is 5 KG / min, and the speed is kept constant for 10 minutes after the feeding is completed. 2-8 parts by weight of a polyurethane glue curing agent with a solid content of 50%-80% is added at a feeding speed of 5 KG / min, and the speed is kept constant for 10 minutes after the feeding is completed, and the mixture is evenly mixed to form the polyurethane glue.
[0032] As a preferred embodiment of the present invention, the specific method of step S5 is as follows:
[0033] S51. Use the coating machine unwinding device to unwind the biaxially oriented polyester film with a thickness of 10-50 μm, and the unwinding speed is 100-200 m / min.
[0034] S52. The surface of the biaxially oriented polyester film with a thickness of 10-50μm is treated by the plasma generator of the coating machine, with a processing power of 5-70KW. A large number of positive and negative ions are generated by ionizing the air with positive and negative high voltages, wherein the number of negative ions is about 1.5 times greater than that of positive ions. The positive and negative ions remove the atoms or molecules adsorbed on the surface of BOPET, obtain ultra-high surface energy, adjust polarity, and create atomic groups or functional groups that can react chemically with polyurethane adhesives, such as polar groups such as hydroxyl, ketone, ether, carbonate, and ester. At the same time, the plasma generator increases the surface tension of the BOPET film, so that the polyurethane glue can be more easily spread on the surface of the film to form a uniform coating, thereby ensuring sufficient bonding strength between the coating and the film.
[0035] S53. The polyurethane glue is applied to the surface of the biaxially oriented polyester film having a thickness of 10-50 μm by a coating device of a coating machine, and the coating amount of the polyurethane glue coating is 0.2-0.5 g / m 2 .
[0036] S54. Use coating machine drying device for drying, drying temperature: 65 ~ 95 ℃, wind speed: 20m / s. Drying tension: 100 ~ 200N.
[0037] S55. The coating liquid is applied to the surface of the biaxially oriented polyester film having a thickness of 10-50 μm by a coating device of a coating machine, and the coating amount of the coating liquid coating is 1.5-3.5 g / m 2 .
[0038] S56. Use the infrared device of the coating machine to dry 70%-80% of the water in the coating liquid. The drying temperature is 100-300℃ and the exhaust wind speed is 20m / s.
[0039] 70%-80% of the coating liquid is water, which needs to be dried and removed. An infrared heating device is installed in front of the hot air dryer. The infrared rays are penetrating and can heat the surface and the inside of the coating layer at the same time, removing 70%-80% of the water in the coating liquid, so that the modified polyvinylidene chloride is quickly dried and fixed, which is beneficial to improve the crystallinity of the modified polyvinylidene chloride. In order to remove the water in the modified polyvinylidene chloride, use far infrared medium wave 2.0-3.0 microns. The exhaust on the infrared heating device is turned on to drain the water so that the water vapor around the device cannot reach the saturated vapor pressure.
[0040] S57. Use the hot air drying device of the coating machine to dry the remaining 20%-30% of the water in the coating liquid. The drying temperature is 85-125°C, the wind speed is 20m / s, and the drying tension is 100-200N.
[0041] S58. Use the coating machine cooling device to cool the film, and the cooling temperature is 20 to 40 °C.
[0042] The coating first contacts the surface of the cooling cylinder when it is hot, so the surface of the cooling cylinder is required to be mirror-like, and any defects will be reflected on the coating surface.
[0043] The temperature of the polyvinylidene chloride coating film coming out of the oven is 80-95℃. The water has evaporated, but the PVDC has not yet fully crystallized and is in an amorphous or amorphous state. The polyvinylidene chloride coating film is a heat-shrinkable plastic and is sticky. If it is directly rolled up, it is easy to cause adhesion and film shrinkage and deformation. Therefore, it must be cooled and rolled up after cooling to 20-30℃. The water temperature of the cooling roller is 15-20℃. Rapidly lowering the coating temperature to room temperature can quickly eliminate the internal stress of the film, and at the same time make the polyvinylidene chloride coating crystallize more finely and form microcrystals. After the film is solidified, it will not stick or pull.
[0044] S59. Use the coating machine winding device to wind the film, and the winding tension is 80~150N.
[0045] S60. The biaxially oriented polyester film is aged by using an aging process at a temperature of 45-65° C. for a time of 12 h to 168 h.
[0046] S61. Use a slitting machine to slit the biaxially oriented polyester film.
[0047] The purpose of curing the polyvinylidene chloride coating film is to cross-link the primer and accelerate the crystallization of the polyvinylidene chloride. The higher the crystallinity of the polyvinylidene chloride, the higher the barrier properties, solvent resistance and anti-adhesion properties of the polyvinylidene chloride coating film.
[0048] It takes 7 to 10 days for polyvinylidene chloride to reach 70% crystallinity at 30°C, and about 15 days for complete crystallization. Increasing the temperature can accelerate the crystallization of PVDC.
[0049] As a preferred embodiment of the present invention, when the biaxially oriented polyester film is coated on both sides, the following steps are continued on the basis of S59:
[0050] S591. Using the coating machine unwinding device to unwind the biaxially oriented polyester film coated on one side, the unwinding speed is 200m / min;
[0051] S592. The uncoated surface of the biaxially oriented polyester film is treated by a plasma generator of a coating machine, with a processing power of 10KW;
[0052] S593. The polyurethane glue is applied to the surface of the film treated by S52 by a coating device of a coating machine, and the coating amount of the polyurethane glue coating is 0.3g / m2 ;
[0053] S594. Drying by coating machine drying device, drying temperature: 65 ~ 95 ℃, wind speed: 20m / s. Drying tension: 100 ~ 200N;
[0054] S595. The coating liquid is applied to the surface of the film treated by S594 by a coating device of a coating machine. The coating amount of the coating liquid is 3.0 g / m 2 ;
[0055] S596. Use the infrared device of the coating machine to dry 70% of the water in the coating liquid, the drying temperature is: 100 ~ 300 ℃, the exhaust wind speed is: 20m / s;
[0056] S597. Use the hot air drying device of the coating machine to dry the remaining 30% of the water in the coating liquid. The drying temperature is 85-125°C, the wind speed is 20m / s, and the drying tension is 100-200N.
[0057] S598. The film is cooled by a coating machine cooling device, the cooling temperature is 20-40°C;
[0058] S599. Use the coating machine winding device to wind the film, and the winding tension is 80~150N.
[0059] As a preferred embodiment of the present invention, the hot air drying device of the coater used in step S57 is an air flotation oven. The temperature of the air flotation oven is controlled by zones. The temperature setting is determined according to the coating thickness and the coating speed. The thicker the coating thickness, the faster the coating speed, and the higher the temperature setting, and vice versa. The temperature interval is 5-20°C, and the instantaneous film temperature is 100-105°C. The instrument indication temperature of the air flotation oven is set at 105-125°C, and the film body temperature is 80-95°C. When the coating thickness and coating speed change, the temperature should be adjusted accordingly. The higher the drying temperature (85-125°C), the easier it is to obtain a dense and continuous coating, the higher the degree of crystallization of the coating, and the better the barrier properties, heat sealing properties, and solvent resistance.
[0060] Compared with the prior art, the method for preparing a solvent-resistant high heat-sealing strength coating film for packaging of the present invention has the following beneficial effects:
[0061] 1. Solve the defect that the coating film is corroded and damaged by solvents or aromatics:
[0062] An accelerator is added to a copolymerized vinylidene chloride emulsion with a medium polymerization degree, and the polyvinylidene chloride emulsion is modified to prepare a modified polyvinylidene chloride emulsion. The coating formed by the modified polyvinylidene chloride has high crystallinity, fine crystal nuclei, and dense coating. The modified polyvinylidene chloride emulsion has good leveling properties, is easy to flatten when coated on a film, and the formed coating is uniform with extremely low roughness, and will not be eroded, swollen, or destroyed by various solvents or aromatics, thereby meeting the packaging requirements of articles containing corrosive solvents or aromatics.
[0063] In addition, the coating formed by the modified polyvinylidene chloride has excellent heat sealing performance, and its heat sealing strength is above 4.0N / 25mm, which is twice that of the currently available coated films and fully meets the requirements of direct bag packaging.
[0064] 2. Solve the defect of low peel strength of coating film:
[0065] A plasma generator is used to treat the surface of the PET film to remove atoms or molecules adsorbed on the surface, obtain ultra-high surface energy, adjust polarity, create atomic groups or functional groups that can chemically react with polyurethane adhesives, such as hydroxyl groups, ketone groups, ether groups, carbonate groups, ester groups and other polar groups, so as to make solvent-resistant polyurethane adhesives and control the coating amount of the adhesive. The above method can produce a coating film with high peel strength, and its peel strength is above 4.0N / 15mm, which is more than twice that of existing coating films.
[0066] 3. Solve the defects of adhesion and additive precipitation during the coating film processing:
[0067] a. Add inorganic nano-silica solution to modified polyvinylidene chloride emulsion. After the coating formed by the mixed solution dries, a part of the nano-silica particles are suspended on the coating surface, and the direct contact area between the films is greatly reduced. When the coated film is rolled up, the air forms countless tiny air cushions between the film layers, which effectively prevents the adhesion between the film layers.
[0068] Another part of the nano-silica particles are embedded in the surface of the coating, making the surface of the film microscopically coarsened and raised. On the one hand, it effectively prevents the adhesion between the film layers. On the other hand, the extremely small protrusions formed by the nano-silica particles create effective friction between the films. The end faces of the films are neat during the winding process. The nano-silica particles are embedded in the surface of the coating, creating a "ball-and-shaft effect". The part exposed outside the coating makes the film scratch-resistant and abrasion-resistant.
[0069] The particle size of the nano-silicon dioxide particles in the coating is between 7 and 40 nanometers. Due to their extremely small particle size, they act as crystal nuclei during the crystallization of modified polyvinylidene chloride, which is beneficial to the crystallization of modified polyvinylidene chloride, thereby making the barrier properties and solvent resistance of the film stronger.
[0070] b. The polyvinylidene chloride emulsion needs to be cooled after drying. The temperature of the dried polyvinylidene chloride coating film is between 80 and 95°C, and only water is evaporated. The polyvinylidene chloride coating film is in an amorphous or amorphous state. The polyvinylidene chloride coating film is a heat-shrinkable plastic and is sticky, so it must be cooled and rolled up after cooling to 20 to 30°C.
[0071] By using a rapid cooling process and controlling the cooling water temperature at 15-20°C, the coating temperature is rapidly reduced to room temperature, which can quickly eliminate the internal stress of the film and make the PVDC crystals more dense to form microcrystals. After the film is cured, it will not stick or pull. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only examples of the embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0073] Figure 1 is a flow chart of an embodiment of the present invention;
[0074] Figure 2 Schematic diagram of a single-sided solvent-resistant thin film coating in an embodiment of the present invention;
[0075] Figure 3 Schematic diagram of double-sided solvent-resistant thin film coating in an embodiment of the present invention. DETAILED DESCRIPTION
[0076] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0077] In the description of the embodiments of the present invention, it should be understood that the terms "upper", "lower", "front", "back", "inside", "outside", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present invention.
[0078] In the description of the embodiments of the present invention, it should be noted that, unless otherwise clearly stipulated and limited, the terms "installation", "connection" and "connection" should be understood in a broad sense. For example, it can be a fixed connection, an integral connection, or a detachable connection; it can be the internal connection of two components; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present invention can be understood according to specific circumstances.
[0079] See attached Figure 1 Shown is a flow chart of the preparation method of the present invention.
[0080] Embodiment 1:
[0081] The present invention provides a method for preparing a solvent-resistant, high heat-sealing strength packaging coated film through the embodiment of the present invention. The steps for preparing a single-sided coated film are as follows:
[0082] The substrate film is a biaxially oriented polyester film (BOPET) with a thickness of 12 μm.
[0083] The main agent of the polyurethane glue is a solvent-resistant polyurethane glue main agent with a solid content of 45%.
[0084] The polyurethane glue curing agent is a solvent-resistant polyurethane glue curing agent with a solid content of 50%.
[0085] The solvent of polyurethane glue is ethyl acetate.
[0086] The coating amount of polyurethane glue coating is 0.2g / m 2 .
[0087] The solid content of polyvinylidene chloride (PVDC) is 40%.
[0088] The accelerator is palm wax.
[0089] The inorganic nano-silicon dioxide has a particle size of 40 nanometers.
[0090] The emulsifier is sodium dodecyl sulfate.
[0091] Distilled water is homemade distilled water.
[0092] The coating amount of the coating liquid is 2.7g / m 2 .
[0093] The coating machine is HTTBJ-1600 coating machine.
[0094] High-speed ball mill is a high-speed vertical stirring ball mill.
[0095] S1. Preparation of modified polyvinylidene chloride (PVDC) emulsion:
[0096] ⑴. Add 89 parts by weight of PVDC emulsion to a stainless steel reactor containing 10 parts by weight of distilled water, and heat to 35°C. Control the pressure at normal pressure, the frequency of the stirrer at 50Hz, and the feeding speed at 45KG / h. After the feeding is completed, keep the temperature and speed constant for 30 minutes.
[0097] ⑵. Keep the temperature and the frequency of the stirrer unchanged, slowly add 1 part of the accelerator by weight into the above solution, and the feeding speed is 10KG / h. After the feeding is completed, keep the temperature and speed constant for 24 hours. After the reaction is fully completed and mixed, vacuumize at low pressure, degas, and prepare a modified polyvinylidene chloride (PVDC) emulsion, and cool it to 20℃ for use.
[0098] S2. Preparation of inorganic nano-silica solution: grind 1 part of inorganic nano-silica with a particle size of 40 nanometers at a low speed and add it to a grinder containing 98.9 parts of distilled water by weight, and add the temperature to 40°C, control the pressure at normal pressure, control the frequency of the grinder at 20Hz, and feed rate at 10KG / h. After the addition is completed, keep the temperature and speed constant for 30 minutes, and slowly add 0.1 parts of emulsifier by weight to the above solution at a feeding rate of 10KG / h. After the addition is completed, keep the temperature and speed constant for 30 minutes. Gradually increase the frequency of the grinder to 50Hz within 1-5 minutes, keep the temperature and speed constant for 60 minutes, so that the inorganic nano-silica is fully dispersed and evenly evacuated at low pressure, deaerated, and made into an inorganic nano-silica solution, cooled to 20°C for use.
[0099] S3. Preparation of coating liquid: Add 1 part of inorganic nano-silicon dioxide solution by weight to a reactor containing 99 parts of modified polyvinylidene chloride (PVDC) emulsion by weight with low-speed stirring, raise the temperature to 35°C, control the pressure at normal pressure, control the frequency of the stirrer at 30Hz, and add the material at a rate of 5KG / h. After the addition is completed, keep the temperature and speed constant for 10 minutes. Then gradually increase the stirrer frequency to 50Hz within 1-2 minutes, keep the temperature and speed constant for 30 minutes, mix the two thoroughly, evacuate at low pressure, degas, make the coating liquid, and cool to 20°C for use.
[0100] S4. Preparation of polyurethane glue: add 20 parts by weight of polyurethane glue main agent with a solid content of 50% to a reactor containing 80 parts by weight of ethyl acetate under low-speed stirring, at room temperature and pressure, control the frequency of the stirrer to 20 Hz, and the feeding rate to 5 kg / min. After the feeding is completed, keep the speed constant for 10 minutes. Then add 4 parts by weight of polyurethane glue curing agent with a solid content of 75% at a feeding rate of 5 kg / min. After the feeding is completed, keep the speed constant for 10 minutes to fully mix and evenly prepare the polyurethane glue for use.
[0101] S5. Use the unwinding device of the coating machine to unwind the biaxially oriented polyester film (BOPET) with a thickness of 12 μm at an unwinding speed of 200 m / min.
[0102] S6. The surface of the biaxially oriented polyester film (BOPET) is treated by a plasma generator of a coating machine with a treatment power of 10KW.
[0103] S7. The polyurethane glue is applied to the surface of the biaxially oriented polyester film treated in step S6 by a coating device of a coating machine, and the coating amount of the polyurethane glue coating is 0.2 g / m 2 .
[0104] S8. Drying is carried out using a coating machine drying device, with a drying temperature of 75°C, a wind speed of 20m / s, and a drying tension of 80N.
[0105] S9. The coating liquid is applied to the surface of the film after the treatment in step S8 by a coating device of a coating machine, and the coating amount of the coating liquid coating is 2.7 g / m 2 .
[0106] S10. Use the infrared device of the coating machine to dry 70% of the water in the coating liquid, the drying temperature is 140℃, and the exhaust wind speed is 20m / s.
[0107] S11. Use the hot air drying device of the coating machine to dry the remaining 30% of the water in the coating liquid, the drying temperature is: 110 ℃, the wind speed is: 20m / s, and the drying tension is: 100N.
[0108] S12. Use the coating machine cooling device to cool the film, cooling temperature: 40 ℃.
[0109] S13. Use the coating machine winding device to wind the film, and the winding tension is 90N.
[0110] S15. The coated film is aged by using an aging process at a temperature of 50° C. for 96 hours.
[0111] S16. Use a slitting machine to slit the coated film.
[0112] The solvent-resistant high heat-seal strength packaging single-sided coated film (see Figure 2 The performance test data is as follows:
[0113] thickness Oxygen permeable moisture permeable Friction coefficient Haze Anti-adhesion Heat seal strength Peel strength Solvent resistance test 14 7.6 6.4 0.45 3 Level 1 4.5 4.8 No cracks
[0114] 1.Thickness: Indicates the thickness of the film. Unit: μm, test standard: GB / T 6672.
[0115] 2. Oxygen permeability: Indicates the amount of oxygen that permeates the film under test conditions. The larger the value, the worse the film's barrier properties. Unit: cm 3 / (m 2 ∙24h), test conditions: 23℃, relative humidity 0%, test standard: ASTM D3985.
[0116] 3. Moisture permeability: Indicates the amount of water vapor that passes through the film under test conditions. The larger the value, the worse the film's barrier properties. Unit: g / (m 2 ∙24h), test conditions: 38℃, relative humidity 90%, test standard: ASTM F1249.
[0117] 4. Friction coefficient: Indicates the smoothness of the film surface. The larger the value, the worse the film's smoothness and the worse the running performance. Unit: None. Test standard: ASTM D1894.
[0118] 5. Haze: Indicates the degree of transparency of the film. The larger the value, the more opaque the film. Unit: %. Test standard: ASTMD1003.
[0119] 6. Anti-adhesion: Characterizes the degree of film adhesion. The grades are divided into 0-5. Grade 0 means weak adhesion and grade 5 means strong adhesion. The larger the grade value, the easier the film is to adhere. Unit: grade. Test standard: GB / T 39935-2021.
[0120] 7. Heat seal strength: It indicates the heat seal strength of the coating under the test conditions. The larger the value, the stronger the coating seal strength, the stronger the bag edge seal strength, and the less likely the bag will break. Unit: N / 25mm. Test conditions: 155℃, 0.5S, 250KPa. Test standard: ASTMF88.
[0121] 8. Peel strength: It indicates the composite strength between the coating and other materials under the test conditions. The larger the value, the greater the composite strength between the coating and other materials, and the composite layers will not come apart. Unit: N / 15mm. Test standard: GB / T 2790-1995.
[0122] 9. Solvent resistance test: characterizes the solvent resistance of the coating under test conditions. Test conditions: 60°C, 7 days.
[0123] Embodiment 2:
[0124] According to the method for preparing a solvent-resistant and high heat-sealing strength packaging coated film according to the second embodiment of the present invention, the steps of preparing the single-sided coated film are as follows:
[0125] The substrate film is a biaxially oriented polyester film (BOPET) with a thickness of 12 μm.
[0126] The main agent of the polyurethane glue is a solvent-resistant polyurethane glue main agent with a solid content of 50%.
[0127] The polyurethane glue curing agent is a solvent-resistant polyurethane glue curing agent with a solid content of 55%.
[0128] The solvent of polyurethane glue is ethyl acetate.
[0129] The coating amount of polyurethane glue coating is 0.3g / m 2 .
[0130] The solid content of polyvinylidene chloride (PVDC) emulsion is 45%.
[0131] The accelerator is palm wax.
[0132] The particle size of inorganic nano-silica is 35 nanometers.
[0133] The emulsifier is sodium dodecyl sulfate.
[0134] Distilled water is homemade distilled water.
[0135] The coating amount of the coating liquid is 3.0g / m 2 .
[0136] The coating machine is HTTBJ-1600.
[0137] High-speed ball mill is a high-speed vertical stirring ball mill.
[0138] The production steps of this embodiment are the same as those of the first embodiment, except that the ratio parameters in each step are as follows:
[0139] S1. Preparation of modified polyvinylidene chloride (PVDC) emulsion:
[0140] 87 parts by weight of PVDC emulsion stirred, 3 parts by weight of accelerator;
[0141] S2. Preparation of inorganic nano-silica solution:
[0142] 3 parts by weight of inorganic nano-silicon dioxide with a particle size of 35 nanometers, 96.7 parts by weight of distilled water, and 0.3 parts by weight of an emulsifier;
[0143] S3. Preparation of coating solution:
[0144] The weight content of the inorganic nano-silicon dioxide solution is 2 parts, and the weight content of the modified polyvinylidene chloride (PVDC) emulsion is 98 parts.
[0145] S4. Preparation of polyurethane glue: add 20 parts by weight of polyurethane glue main agent with a solid content of 50% to a reactor containing 80 parts by weight of ethyl acetate under low-speed stirring, at room temperature and pressure, control the frequency of the stirrer to 20 Hz, and the feeding rate to 5 KG / min. After the feeding is completed, keep the speed constant for 10 minutes. Then add 4 parts by weight of polyurethane glue curing agent with a solid content of 55% at a feeding rate of 5 KG / min. After the feeding is completed, keep the speed constant for 10 minutes to fully mix and evenly prepare the polyurethane glue for use.
[0146] S5. Use the unwinding device of the coating machine to unwind the biaxially oriented polyester film (BOPET) with a thickness of 12 μm at an unwinding speed of 200 m / min.
[0147] S6. The surface of the biaxially oriented polyester film (BOPET) is treated by a plasma generator of a coating machine with a treatment power of 10KW.
[0148] S7. The polyurethane glue is applied to the surface of the biaxially oriented polyester film after the treatment in step S6 by a coating device of a coating machine, and the coating amount of the polyurethane glue coating is 0.3 g / m 2 .
[0149] S8. Drying is performed using a coating machine drying device, with a drying temperature of 80°C, a wind speed of 20m / s, and a drying tension of 90N.
[0150] S9. The coating liquid is applied to the surface of the film treated in step S8 by a coating device of a coating machine, and the coating amount of the coating liquid coating is 3.0 g / m 2 .
[0151] S10. Use the infrared device of the coating machine to dry 70% of the water in the coating liquid, the drying temperature is 150℃, and the exhaust wind speed is 20m / s.
[0152] S11. Use the hot air drying device of the coating machine to dry the remaining 30% of the water in the coating liquid, the drying temperature is: 115 ℃, the wind speed is: 20m / s, and the drying tension is: 110N.
[0153] S12. Use the coating machine cooling device to cool the film, cooling temperature: 35 ℃.
[0154] S13. Use the coating machine winding device to wind the film, and the winding tension is 95N.
[0155] S15. The coated film is aged by using an aging process at a temperature of 50° C. for 120 hours.
[0156] S16. Use a slitting machine to slit the coated film.
[0157] Under the same test conditions as in Example 1, the performance test data of the single-sided coated film for packaging with high heat-seal strength and resistance to solvent corrosion prepared by the method of Example 2 are as follows:
[0158] thickness Oxygen permeable moisture permeable Friction coefficient Haze Anti-adhesion Heat seal strength Peel strength Solvent resistance test 14 6.9 5.8 0.4 2.8 Level 1 4.2 4.5 No cracks
[0159] The performance test data of the single-sided coated film prepared by the above-mentioned embodiment 1 and embodiment 2 of the present invention and the single-sided coated film of the same thickness obtained by the prior art solution are compared as follows:
[0160] sample thickness Oxygen permeable moisture permeable Friction coefficient Haze Anti-adhesion Heat seal strength Peel strength Solvent resistance test Sample 1 14 15 12 0.65 4.0 Level 3 1.0 0.8 Cracking, delamination Sample 2 14 13 10 0.55 3.8 Level 3 1.2 1.2 Cracking, delamination Example 1 14 7.6 6.4 0.45 3.0 Level 1 4.5 4.8 No cracks Example 2 14 6.9 5.8 0.40 2.8 Level 1 4.2 4.5 No cracks
[0161] Performance test data analysis:
[0162] 1. Oxygen permeability: The values of Example 1 and Example 2 are both smaller than those of Comparative Sample 1 and Comparative Sample 2, indicating that the oxygen barrier performance of the films of Example 1 and Example 2 is better than that of the above-mentioned comparative samples.
[0163] 2. Moisture permeability: The values of Example 1 and Example 2 are both smaller than those of Comparative Sample 1 and Comparative Sample 2, indicating that the moisture barrier properties of the films of Example 1 and Example 2 are better than those of the above-mentioned comparative samples.
[0164] 3. Friction coefficient: The values of Example 1 and Example 2 are both smaller than those of Comparative Sample 1 and Comparative Sample 2, indicating that the films of Example 1 and Example 2 are smoother and have better running performance.
[0165] 4. Haze: The values of Example 1 and Example 2 are both smaller than those of Comparative Sample 1 and Comparative Sample 2, indicating that the films of Example 1 and Example 2 are more transparent.
[0166] 5. Anti-adhesion: The levels of Example 1 and Example 2 are both lower than those of Comparative Sample 1 and Comparative Sample 2, indicating that the films of Example 1 and Example 2 are not prone to adhesion.
[0167] 6. Heat-sealing strength: The values of Example 1 and Example 2 are greater than those of Comparative Sample 1 and Comparative Sample 2, indicating that the heat-sealing strength of the films of Example 1 and Example 2 is higher.
[0168] 7. Peel strength: The values of Example 1 and Example 2 are greater than those of Comparative Sample 1 and Comparative Sample 2, indicating that the film peel strength of Example 1 and Example 2 is higher, and the coating is less likely to be peeled or delaminated.
[0169] 8. In the solvent resistance test, the films of Example 1 and Example 2 of the present invention showed no cracks, while the films of Comparative Sample 1 and Comparative Sample 2 showed cracks and delamination.
[0170] From the above comparative test data, it can be seen that the single-sided coated film prepared according to the method for preparing a solvent-resistant high heat-sealing strength packaging coated film of the present invention has various properties that are superior to those of the same type of single-sided coated films.
[0171] Embodiment three:
[0172] According to the method for preparing a solvent-resistant high heat-seal strength packaging coating film according to the third embodiment of the present invention, the steps of preparing the double-sided coating film are as follows:
[0173] The substrate film is a biaxially oriented polyester film (BOPET) with a thickness of 12 μm.
[0174] The main agent of the polyurethane glue is a solvent-resistant polyurethane glue main agent with a solid content of 55%.
[0175] The polyurethane glue curing agent is a solvent-resistant polyurethane glue curing agent with a solid content of 60%.
[0176] The solvent of polyurethane glue is ethyl acetate.
[0177] The coating amount of polyurethane glue coating is 0.4g / m 2 .
[0178] The solid content of polyvinylidene chloride (PVDC) emulsion is 47%.
[0179] The accelerator is palm wax.
[0180] The particle size of inorganic nano-silica is 30 nanometers.
[0181] The emulsifier is sodium dodecyl sulfate.
[0182] Distilled water is homemade distilled water.
[0183] The coating amount of the front coating liquid is 2.2g / m 2 .
[0184] The coating amount of the reverse coating liquid is 3.2 g / m 2 .
[0185] The coating machine is HTTBJ-1600.
[0186] High-speed ball mill is a high-speed vertical stirring ball mill.
[0187] S1. Preparation of modified polyvinylidene chloride (PVDC) emulsion:
[0188] ⑴. Stir 85 parts of PVDC emulsion into a stainless steel reactor containing 10 parts of distilled water, raise the temperature to 35°C, control the pressure at normal pressure, control the frequency of the stirrer at 50Hz, and feed rate at 45KG / h. After the addition is completed, keep the temperature and speed constant for 30 minutes.
[0189] ⑵. Keep the temperature and the frequency of the stirrer unchanged, slowly add 5 parts of the accelerator by weight into the above solution, and the feeding speed is 10KG / h. After the addition is completed, keep the temperature and speed constant for 24 hours to make it react fully and mix evenly, then vacuumize at low pressure, degas, and make a modified polyvinylidene chloride (PVDC) emulsion, cool to 20℃, and set aside.
[0190] S2. Preparation of inorganic nano silicon dioxide solution: grind 3 parts of inorganic nano silicon dioxide with a particle size of 30 nanometers at low speed and add it to a grinder containing 96.7 parts of distilled water by weight, add the temperature to 40°C, control the pressure at normal pressure, control the frequency of the grinder at 20Hz, and feed rate to 10KG / h. After the feeding is completed, keep constant temperature and speed for 30min, slowly add 0.3 parts of emulsifier by weight to the solution, and feed rate to 10KG / h. After the feeding is completed, keep constant temperature and speed for 30min, gradually increase the frequency of the grinder to 50Hz within 1-5min, keep constant temperature and speed for 60min, make the inorganic nano silicon dioxide fully dispersed and evenly vacuumized at low pressure, deaerate, make inorganic nano silicon dioxide solution, cool to 20°C, and set aside.
[0191] S3. Preparation of coating liquid: Add 3 parts of inorganic nano-silicon dioxide solution by weight into a reactor containing 97 parts of modified polyvinylidene chloride (PVDC) emulsion by weight with low-speed stirring, raise the temperature to 35°C, control the pressure at normal pressure, control the stirrer frequency at 30Hz, and the feeding rate at 5KG / h. After the feeding is completed, keep the temperature and speed constant for 10 minutes. Gradually increase the stirrer frequency to 50Hz within 1-2 minutes, keep the temperature and speed constant for 30 minutes, make the two fully mixed, vacuumize at low pressure, degas, make the coating liquid, cool to 20°C, and set aside.
[0192] S4. Preparation of polyurethane glue: add 20 parts by weight of polyurethane glue main agent with a solid content of 55% to a reactor containing 80 parts by weight of ethyl acetate with low-speed stirring, at room temperature and pressure, control the frequency of the stirrer to 20 Hz, the feeding rate to 5 KG / min, and keep it stable at a constant speed for 10 minutes after the addition is completed, add 4 parts by weight of polyurethane glue curing agent with a solid content of 60%, and the feeding rate to 5 KG / min, and keep it stable at a constant speed for 10 minutes after the addition is completed, so that it is fully mixed and evenly formed into polyurethane glue for use.
[0193] S5. Use the unwinding device of the coating machine to unwind the biaxially oriented polyester film (BOPET) with a thickness of 12 μm at an unwinding speed of 200 m / min.
[0194] S6. The front side of the biaxially oriented polyester film (BOPET) is treated by a plasma generator of a coating machine with a treatment power of 10KW.
[0195] S7. The polyurethane glue is applied to the front of the film after the treatment in step S6 by a coating device of a coating machine, and the coating amount of the polyurethane glue coating is 0.4 g / m 2 .
[0196] S8. Drying is carried out using a coating machine drying device, with a drying temperature of 85°C, a wind speed of 20m / s, and a drying tension of 120N.
[0197] S9. The coating liquid is applied to the surface of the film treated in step S8 by a coating device of a coating machine, and the coating amount of the coating liquid coating is 2.2 g / m 2 .
[0198] S10. Use the infrared device of the coating machine to dry 70% of the water in the coating liquid, the drying temperature is 155℃, and the exhaust wind speed is 20m / s.
[0199] S11. Use the hot air drying device of the coating machine to dry the remaining 30% of the water in the coating liquid. The drying temperature is 125°C, the wind speed is 20m / s, and the drying tension is 120N.
[0200] S12. Use the coating machine cooling device to cool the film, cooling temperature: 30 ℃.
[0201] S13. Use the coating machine winding device to wind the film, and the winding tension is 120N.
[0202] S14. Use the coating machine unwinding device to unwind the biaxially oriented polyester film (BOPET) coated with the coating liquid, with an unwinding speed of 200m / min.
[0203] S15. The uncoated reverse side is treated by the plasma generator of the coater, with a processing power of 10KW.
[0204] S16. The polyurethane glue is applied to the reverse side of the biaxially oriented polyester film treated by S15 by means of a coating device of a coating machine, and the coating amount of the polyurethane glue coating is 0.4 g / m 2 .
[0205] S17. Drying is performed using a coating machine drying device, with a drying temperature of 85°C, a wind speed of 20m / s, and a drying tension of 120N.
[0206] S18. The coating liquid is applied to the reverse side of the film treated by S17 by a coating device of a coating machine, and the coating amount of the coating liquid coating is 3.2 g / m 2 .
[0207] S19. Use the infrared device of the coating machine to dry 70% of the water in the coating liquid. The drying temperature is 155°C and the exhaust wind speed is 20m / s.
[0208] S20. Use the hot air drying device of the coating machine to dry the remaining 30% of the water in the coating liquid, the drying temperature is: 125 ℃, the wind speed is: 20m / s, and the drying tension is: 120N.
[0209] S21. Use the coating machine cooling device to cool the film, cooling temperature: 30 ℃.
[0210] S22. Use the coating machine winding device to wind the film, and the winding tension is 120N.
[0211] S23. The film is cured by using a curing process at a temperature of 50° C. for 144 hours.
[0212] S24. Use a slitting machine to slit the film.
[0213] Under the same test conditions as in Example 1, the solvent-resistant high heat-seal strength double-sided coated film for packaging (see Figure 3 The performance test data is as follows:
[0214] thickness Oxygen permeable moisture permeable Friction coefficient Haze Anti-adhesion Heat seal strength Peel strength Solvent resistance test 15 5.2 5 0.35 2.5 Level 0 4.6 5 No cracks
[0215] Embodiment 4:
[0216] According to the method for preparing a solvent-resistant high heat-seal strength packaging coating film according to the fourth embodiment of the present invention, the steps of preparing the double-sided coating film are as follows:
[0217] The substrate film is a biaxially oriented polyester film (BOPET) with a thickness of 12 μm.
[0218] The main agent of the polyurethane glue is a solvent-resistant polyurethane glue main agent with a solid content of 60%.
[0219] The polyurethane glue curing agent is a solvent-resistant polyurethane glue curing agent with a solid content of 75%.
[0220] The solvent of polyurethane glue is ethyl acetate.
[0221] The coating amount of polyurethane glue coating is 0.5g / m 2 .
[0222] The solid content of polyvinylidene chloride (PVDC) emulsion is 50%.
[0223] The accelerator is palm wax.
[0224] The particle size of inorganic nano-silica is 25 nanometers.
[0225] The emulsifier is sodium dodecyl sulfate.
[0226] Distilled water is homemade distilled water.
[0227] The coating amount of the front coating liquid is 2.5g / m 2 .
[0228] The coating amount of the reverse coating liquid is 3.5 g / m 2 .
[0229] The coating machine is HTTBJ-1600.
[0230] High-speed ball mill is a high-speed vertical stirring ball mill.
[0231] The production steps of this embodiment are the same as those of the third embodiment, except that the ratio parameters in each step are as follows:
[0232] S1. Preparation of modified polyvinylidene chloride (PVDC) emulsion:
[0233] Using 83 parts by weight of PVDC emulsion and 7 parts by weight of accelerator;
[0234] S2. Preparation of inorganic nano-silica solution:
[0235] Using 4 parts by weight of inorganic nano-silicon dioxide with a particle size of 25 nanometers, 95.6 parts by weight of distilled water, and 0.4 parts by weight of an emulsifier;
[0236] S3. Preparation of coating solution:
[0237] Using 4 parts by weight of inorganic nano-silicon dioxide solution and 96 parts by weight of modified polyvinylidene chloride (PVDC) emulsion;
[0238] S4. Preparation of polyurethane glue:
[0239] Use 20 parts by weight of a polyurethane glue main agent with a solid content of 60%, 80 parts by weight of ethyl acetate, and 4 parts by weight of a polyurethane glue curing agent with a solid content of 75%;
[0240] S5. Use the unwinding device of the coating machine to unwind the biaxially oriented polyester film (BOPET) with a thickness of 12 μm at an unwinding speed of 200 m / min.
[0241] S6. The surface of the biaxially oriented polyester film (BOPET) is treated by a plasma generator of a coating machine with a treatment power of 10KW.
[0242] S7. The polyurethane glue is applied to the front of the biaxially oriented polyester film treated by S6 through the coating device of the coating machine, and the coating amount of the polyurethane glue coating is 0.5g / m 2 .
[0243] S8. Drying is performed using a coating machine drying device, with a drying temperature of 90°C, a wind speed of 20m / s, and a drying tension of 130N.
[0244] S9. The coating liquid is applied to the front side of the film treated by S8 by a coating device of a coating machine, and the coating amount of the coating liquid is 2.5 g / m 2 .
[0245] S10. Use the infrared device of the coating machine to dry 70% of the water in the coating liquid, the drying temperature is 160℃, and the exhaust wind speed is 20m / s.
[0246] S11. Use the hot air drying device of the coating machine to dry the remaining 30% of the water in the coating liquid. The drying temperature is 125°C, the wind speed is 20m / s, and the drying tension is 125N.
[0247] S12. Use the coating machine cooling device to cool the film, cooling temperature: 25 ℃.
[0248] S13. Use the coating machine winding device to wind the film, and the winding tension is 125N.
[0249] S14. Use the coating machine unwinding device to unwind the biaxially oriented polyester film (BOPET) coated with the coating liquid, with an unwinding speed of 200m / min.
[0250] S15. The uncoated reverse side is treated by the plasma generator of the coater, with a processing power of 10KW.
[0251] S16. The polyurethane glue is applied to the reverse side of the biaxially oriented polyester film treated by S15 by means of a coating device of a coating machine, and the coating amount of the polyurethane glue coating is 0.5 g / m 2 .
[0252] S17. Drying is performed using a coating machine drying device, with a drying temperature of 85°C, a wind speed of 20m / s, and a drying tension of 130N.
[0253] S18. The coating liquid is applied to the reverse side of the film treated by S17 by a coating device of a coating machine, and the coating amount of the coating liquid is 3.5 g / m 2 .
[0254] S19. Use the infrared device of the coating machine to dry 70% of the water in the coating liquid. The drying temperature is 160℃ and the exhaust wind speed is 20m / s.
[0255] S20. Use the hot air drying device of the coating machine to dry the remaining 30% of the water in the coating liquid, the drying temperature is: 125 ℃, the wind speed is: 20m / s, and the drying tension is: 125N.
[0256] S21. Use the coating machine cooling device to cool the film, cooling temperature: 25 ℃.
[0257] S22. Use the coating machine winding device to wind the film, and the winding tension is 125N.
[0258] S23. The film is aged by using an aging process at a temperature of 50° C. for 168 hours.
[0259] S24. Use a slitting machine to slit the film.
[0260] Under the same test conditions as in Example 1, the performance test data of the double-sided coated film for packaging with high heat-seal strength and resistance to solvent corrosion prepared by the method of Example 4 are as follows:
[0261] thickness Oxygen permeable moisture permeable Friction coefficient Haze Anti-adhesion Heat seal strength Peel strength Solvent resistance test 15 4.5 4 0.3 2 Level 0 5 5.2 No cracks
[0262] The specific performance test data of the double-sided coated film prepared by the above Example 3 and Example 4 and the film of the same thickness are compared as follows:
[0263] sample thickness Oxygen permeable moisture permeable Friction coefficient Haze Anti-adhesion Heat seal strength Peel strength Solvent resistance test Comparative sample 3 15 10 10 0.5 3.6 Level 2 1.5 1.2 Cracking, delamination Comparative sample 4 15 8.2 7.5 0.45 3.2 Level 2 1.5 1.5 Cracking, delamination Example 3 15 5.2 5 0.35 2.5 Level 0 4.6 5 No cracks Example 4 15 4.5 4 0.3 2 Level 0 5 5.2 No cracks
[0264] Test data analysis:
[0265] 1. Oxygen permeability: The values of Examples 3 and 4 are both smaller than those of Comparative Samples 3 and 4, indicating that the oxygen barrier properties of the films of Examples 3 and 4 are better than those of the above-mentioned comparative samples.
[0266] 2. Moisture permeability: The values of Examples 3 and 4 are both smaller than those of Comparative Samples 3 and 4, indicating that the moisture barrier properties of the films of Examples 3 and 4 are better than those of the above-mentioned comparative samples.
[0267] 3. Friction coefficient: The values of Example 3 and Example 4 are both smaller than those of Comparative Sample 3 and Comparative Sample 4, indicating that the films of Example 3 and Example 4 are smoother and have better running performance.
[0268] 4. Haze: The values of Examples 3 and 4 are both smaller than those of Comparative Samples 3 and 4, indicating that the films of Examples 3 and 4 are more transparent.
[0269] 5. Anti-adhesion: The levels of Examples 3 and 4 are lower than those of Comparative Samples 3 and 4, indicating that the films of Examples 3 and 4 are not prone to adhesion.
[0270] 6. Heat-sealing strength: The values of Examples 3 and 4 are greater than those of Comparative Samples 3 and 4, indicating that the heat-sealing strength of the films of Examples 3 and 4 is higher.
[0271] 7. Peel strength: The values of Examples 3 and 4 are greater than those of Comparative Samples 3 and 4, indicating that the film peel strengths of Examples 3 and 4 are higher, and the coatings are less likely to be peeled or delaminated.
[0272] 8. In the solvent resistance test, the films of Example 3 and Example 4 of the present invention showed no cracks, while the films of Comparative Samples 3 and 4 showed cracks and delamination.
[0273] From the above comparative test data, it can be seen that the double-sided coated film prepared according to the method for preparing a solvent-resistant high heat-sealing strength packaging coated film of the present invention has various properties that are superior to those of the same type of double-sided coated films.
[0274] The above shows and describes the basic principles of the present invention. The above are only preferred embodiments of the present invention and are not intended to limit the present invention. The above embodiments and descriptions in the specification are only intended to illustrate the principles of the present invention. Without departing from the scope of the present invention, any modifications, equivalent substitutions and improvements made within the spirit and scope of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a solvent-resistant high heat-seal strength coating film for packaging, characterized in that: The following steps are involved: S1. Preparation of modified polyvinylidene chloride emulsion, the modified polyvinylidene chloride emulsion comprising 80-89 parts by weight of copolymerized vinylidene chloride emulsion having a solid content of 40%-50% in polymerization degree, 10 parts by weight of distilled water, 1-10 parts by weight of accelerator, and mixed raw materials; S2. Preparation of an inorganic nano-silica solution, wherein the inorganic nano-silica solution comprises 1-10 parts by weight of inorganic nano-silica, 87-98.9 parts by weight of distilled water, and 0.1-3 parts by weight of an emulsifier, wherein the raw materials are dispersed and mixed by high-speed ball milling, and the particle size of the inorganic nano-silica is 7-40 nanometers; S3 prepares a coating solution, the coating solution comprises 90-99.5 parts by weight of the modified polyvinylidene chloride emulsion obtained in S1, 0.5-10 parts by weight of the inorganic nano-silica solution obtained in S2, and is dispersed and mixed at a high speed; S4. Prepare polyurethane glue, the polyurethane glue comprising 10-40 parts by weight of a polyurethane main agent, 2-8 parts by weight of a polyurethane curing agent, and 40-100 parts by weight of ethyl acetate raw materials dispersed and mixed at a low speed; S5. The coating liquid obtained in S3 is coated on the surface of the biaxially oriented polyester film treated by a plasma generator and pre-coated with the polyurethane glue obtained in S4 by a coating machine, and a coated film is prepared by infrared dehydration and hot air drying.
2. The method for preparing a solvent-resistant high heat-seal strength packaging coating film according to claim 1, characterized in that: The biaxially stretched polyester film is divided into single-sided coating and double-sided coating. Single-sided coating is to coat the coating liquid obtained by S3 on any one surface of the biaxially stretched polyester film, and double-sided coating is to coat the coating liquid obtained by S3 on both sides of the biaxially stretched polyester film.
3. The method for preparing a solvent-resistant high heat-seal strength packaging coating film according to claim 2, characterized in that: The specific method for preparing the modified polyvinylidene chloride emulsion in step S1 is as follows: S11, adding 80-89 parts by weight of polyvinylidene chloride emulsion to a stainless steel reactor containing 10 parts by weight of distilled water with stirring, raising the temperature to 35°C, controlling the pressure at normal pressure, the frequency of the stirrer to 50Hz, the feeding speed to 45KG / h, and maintaining the temperature and speed constant for 30 minutes after the feeding is completed; S12, keeping the temperature and the frequency of the agitator unchanged, slowly add 1-10 parts by weight of the accelerator to the solution obtained in the above S11, the feeding rate is 10KG / h, and after the feeding is completed, keep the temperature and speed constant for 24 hours, mix evenly, evacuate at low pressure, degas, make a modified polyvinylidene chloride emulsion, and cool to 20°C.
4. The method for preparing a solvent-resistant high heat-seal strength packaging coating film according to claim 3, characterized in that: The specific method of preparing the inorganic nano-silicon dioxide solution in step S2 is as follows: Inorganic nano silicon dioxide with a content of 1-10 parts by weight and a particle size of 7-40 nanometers is ground at a low speed and added to a grinder containing 87-98.9 parts by weight of distilled water, the temperature is raised to 40°C, the pressure is controlled at normal pressure, the grinder frequency is 20Hz, the feeding speed is 10KG / h, and after the feeding is completed, the temperature and speed are kept constant for 30 minutes. An emulsifier with a content of 0.1-3 parts by weight is slowly added to the above solution at a feeding speed of 10KG / h. After the feeding is completed, the temperature and speed are kept constant for 30 minutes. The grinder frequency is increased to 50Hz within 1-5 minutes, and the temperature and speed are kept constant for 60 minutes. After the inorganic nano silicon dioxide is fully and evenly dispersed, low-pressure vacuuming is performed to degas, and an inorganic nano silicon dioxide solution is prepared, which is then cooled to 20°C.
5. The method for preparing a solvent-resistant high heat-seal strength packaging coating film according to claim 4, characterized in that: The specific method of preparing the coating liquid in step S3 is as follows: An inorganic nano-silicon dioxide solution with a content of 0.5-10 parts by weight is added to a reactor containing a content of 90-99.5 parts by weight of a modified polyvinylidene chloride emulsion with low-speed stirring, the temperature is raised to 35°C, the pressure is controlled at normal pressure, the stirrer frequency is controlled at 30Hz, the feeding rate is 5KG / h, and after the feeding is completed, the temperature and speed are kept constant for 10 minutes, the stirrer frequency is increased to 50Hz within 1-2 minutes, and the temperature and speed are kept constant for 30 minutes. After mixing evenly, low-pressure vacuum is evacuated to degas, a coating liquid is prepared, and the coating liquid is cooled to 20°C.
6. The method for preparing a solvent-resistant high heat-seal strength packaging coating film according to claim 5, characterized in that: The specific method of preparing polyurethane glue in step S4 is as follows: 10-40 parts by weight of a polyurethane glue main agent with a solid content of 40%-60% is added to a reactor containing 40-100 parts by weight of ethyl acetate with low-speed stirring, at room temperature and pressure, the frequency of the stirrer is controlled at 20 Hz, the feeding speed is 5 KG / min, and the speed is kept constant for 10 minutes after the feeding is completed. Then, 2-8 parts by weight of a polyurethane glue curing agent with a solid content of 50%-80% is added at a feeding speed of 5 KG / min. After the feeding is completed, the speed is kept constant for 10 minutes, and the mixture is evenly mixed to form the polyurethane glue.
7. The method for preparing a solvent-resistant high heat-seal strength packaging coating film according to claim 6, characterized in that: The specific method of step S5 is as follows: S51. Using a coating machine unwinding device to unwind a biaxially oriented polyester film having a thickness of 10-50 μm, the unwinding speed is 100 to 200 m / min; S52. The surface of the biaxially oriented polyester film is treated by a plasma generator of a coating machine, with a processing power of 5 to 70 KW; S53. Apply two-component polyurethane glue to the surface of the film treated by S52 through a coating device of a coating machine, and the coating amount of the polyurethane glue coating is 0.2-0.5g / m 2 ; S54. Drying by coating machine drying device, drying temperature: 65 ~ 95 ℃, wind speed: 20m / s. Drying tension: 100 ~ 200N; S55. The coating liquid is applied to the surface of the film treated by S54 by a coating device of a coating machine, and the coating amount of the coating liquid coating is 1.5-3.5g / m 2 ; S56. Use the infrared device of the coating machine to dry 70%-80% of the water in the coating liquid, the drying temperature is 100-300 ° C, and the exhaust wind speed is 20m / s; S57. The remaining 20%-30% of the water in the coating liquid is dried by a hot air drying device of the coating machine, the drying temperature is 85 to 125°C, the wind speed is 20m / s, and the drying tension is 100 to 200N; S58. Cooling the film using a coating machine cooling device, the cooling temperature is 20 to 40 ° C; S59. The film is rolled up by a coating machine winding device, and the winding tension is 80 to 150N; S60. The biaxially oriented polyester film is aged by a aging process at a temperature of 45-65° C. for a time of 12 h to 168 h; S61. Use a slitting machine to slit the biaxially oriented polyester film.
8. The method for preparing a solvent-resistant high heat-seal strength packaging coating film according to claim 7, characterized in that: When the biaxially oriented polyester film is coated on both sides, the steps are as follows based on S59: S591. Using the coating machine unwinding device to unwind the biaxially oriented polyester film coated on one side, the unwinding speed is 200m / min; S592. The uncoated surface of the biaxially oriented polyester film is treated by a plasma generator of a coating machine, with a processing power of 10KW; S593. The polyurethane glue is applied to the surface of the film treated by S592 by a coating device of a coating machine. The coating amount of the polyurethane glue coating is 0.3 g / m 2 ; S594. Drying by coating machine drying device, drying temperature: 65 ~ 95 ℃, wind speed: 20m / s. Drying tension: 100 ~ 200N; S595. The coating liquid is applied to the surface of the film treated by S594 by a coating device of a coating machine. The coating amount of the coating liquid is 3.0 g / m 2 ; S596. Use the infrared device of the coating machine to dry 70% of the water in the coating liquid, the drying temperature is: 100 ~ 300 ℃, the exhaust wind speed is: 20m / s; S597. Use the hot air drying device of the coating machine to dry the remaining 30% of the water in the coating liquid. The drying temperature is 85-125°C, the wind speed is 20m / s, and the drying tension is 100-200N. 9.S598. Use the coating machine cooling device to cool the film, cooling temperature: 20 ~ 40 ℃; S599. Use the coating machine winding device to wind the film, and the winding tension is 80~150N.
10. The method for preparing a solvent-resistant high heat-seal strength packaging coating film according to claim 7, characterized in that: The hot air drying device of the coating machine used in step S57 is an air flotation oven, the temperature of which is controlled by zones, with a temperature interval of 5-20°C and an instantaneous film temperature of 100-105°C.
